2009
DOI: 10.1111/j.1464-5491.2009.02845.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gestational diabetes mellitus in Chinese women—a prospective study of 16 286 pregnant women in China

Abstract: In this large study of GDM in Chinese women, advanced maternal age, pre-pregnancy overweight or obesity and family history of diabetes were confirmed to be risk factors. In addition, a history of recurrent vulvovaginal candidiasis or spontaneous abortion and residency in south China appeared to be novel risk factors in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
87
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 30 publications
10
87
4
3
Order By: Relevance
“…In this study, GA levels strongly correlated with the A1C levels in both GDM and NGT women and these glycated proteins also correlated with FPG and PPG, similar to the observation of Yang et al and Abe et al [10,12]. Hashimoto K et al [14] documented that A1C but not GA was elevated because of iron deficiency anemia in late pregnancy in diabetic women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, GA levels strongly correlated with the A1C levels in both GDM and NGT women and these glycated proteins also correlated with FPG and PPG, similar to the observation of Yang et al and Abe et al [10,12]. Hashimoto K et al [14] documented that A1C but not GA was elevated because of iron deficiency anemia in late pregnancy in diabetic women.…”
Section: Discussionsupporting
confidence: 90%
“…Obesity and advanced age are the risk factors for the development of GDM [10]. In this study also, these factors were observed as risk factors for GDM.…”
Section: Discussionsupporting
confidence: 71%
“…15~13.17) and 6.54 (2.42~17.69), respectively. This finding was consistent with previous studies [17,18]. In addition, spontaneous abortion frequency and history of menstrual cycle disorder were significantly associated with an elevated GDM risk.…”
Section: Discussionsupporting
confidence: 93%
“…However, there were only a few studies reporting the prevalence and risk factors of GDM in China [17,18]. Of particular note, the studies towards the central and western regions of China were lacked.…”
Section: Introductionmentioning
confidence: 99%
“…In the world, the global incidence is actually estimated from 1% to 14% according to the studied population and based on the choice and the moment of the gestational diabetes diagnosis. [2][3][4][5] Pregnancy is associated with important changes concerning the whole of metabolism allowing growth of fetoplacental unit. 6,7 The variations on the cardiovascular, hemodynamic, hematologic, hormonal and hepatic level may have a potential interaction with the physiopathology of gestational diabetes.…”
Section: Introductionmentioning
confidence: 99%